Scleroderma en coup de sabre treated with polymethylmethacrylate - Case report - Joanna Pimenta de Araujo Franco; Márcio Soares Serra; Ricardo Barbosa Lima; Antônio Macedo D'Acri; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2016)
Abstract The scleroderma en coup de sabre is a variant of localized scleroderma that occurs preferentially in children. The disease progresses with a proliferative and inflammatory phase and later atrophy and residual deformity, which are treated with surgical techniques such as injectable fillers, transplanted or autologous fat grafting and resection of the lesion. Among the most widely used fillers is hyaluronic acid. However, there are limitations that motivate the search for alternatives, such as polymethylmethacrylate, a permanent filler that is biocompatible, non-toxic, non-mutagenic and immunologically inert. In order to illustrate its application, a case of scleroderma en coup de sabre in a 17-year-old patient, who was treated with polymethylmethacrylate with excellent aesthetic results, is reported.